2007
DOI: 10.1016/j.jfa.2006.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Unimodular Fourier multipliers for modulation spaces

Abstract: We investigate the boundedness of unimodular Fourier multipliers on modulation spaces. Surprisingly, the multipliers with general symbol e i|ξ | α , where α ∈ [0, 2], are bounded on all modulation spaces, but, in general, fail to be bounded on the usual L p -spaces. As a consequence, the phase-space concentration of the solutions to the free Schrödinger and wave equations are preserved. As a byproduct, we also obtain boundedness results on modulation spaces for singular multipliers |ξ | −δ sin(|ξ | α ) for 0 δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
310
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(316 citation statements)
references
References 26 publications
5
310
0
1
Order By: Relevance
“…They arise when solving the Cauchy problem for dispersive equations. For example, for the solution u(t, x) of the Cauchy problem (1) i∂ t u + |∆| α/2 u = 0, [18,20]). It is then natural to study boundedness properties on other function spaces arising in Fourier analysis.…”
Section: A Fourier Multiplier In Rmentioning
confidence: 99%
See 1 more Smart Citation
“…They arise when solving the Cauchy problem for dispersive equations. For example, for the solution u(t, x) of the Cauchy problem (1) i∂ t u + |∆| α/2 u = 0, [18,20]). It is then natural to study boundedness properties on other function spaces arising in Fourier analysis.…”
Section: A Fourier Multiplier In Rmentioning
confidence: 99%
“…It is then natural to study boundedness properties on other function spaces arising in Fourier analysis. This was recently done in [1] for the modulation spaces M p,q , 1 ≤ p, q ≤ ∞. These spaces were first introduced by Feichtinger [10,11] to measure smoothness of a function or distribution in a way different from Besov spaces, and they are now recognized as a useful tool for studying pseudodifferential operators (see [14,22,25] [15,25,28]).…”
Section: A Fourier Multiplier In Rmentioning
confidence: 99%
“…In other terms, estimate (7) contains information on the oscillations in x of the solution, which cannot be extracted from (2).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, the unimodular Fourier multiplier is not a bounded operator on any L q in general except for q = 2. However, a recent work by Bényi-Gröchenig-Okoudjou-Rogers [1] has shown that e −it(−∆) κ/2 with κ ∈ [0, 2] preserves the M p,qnorm for any 1 p, q ∞, which is proved by the stationary phase method. More precisely, we have the estimate…”
Section: Introduction and Main Resultsmentioning
confidence: 98%